Cuidamos nuestro ambiente, como se genera la basura - Tocto Flores, Nélida Soledad (2019)
The session entitled We take care of our environment, how is garbage generated, was developed in the area of Social Personnel, taking into account the competition responsibly manages the space and the environment. Capacity has been considered Generate actions to conserve the local and global environment. In this learning session it has been possible to achieve the performance. It mentions the environmental problems that affect your daily space (contamination by garbage and waste) and the effects of these on your life; Participate in simple actions aimed at caring for your environment._x000D_ Within the thematic body documents related to environmental problems, solid waste, effects of environmental problems and actions for environmental care have been considered. For the preparation and execution of the learning session, pedagogical processes such as motivation and exploration of previous knowledge, problematization, purpose and organization, management and accompaniment of learning, and evaluation have been taken into account. In addition, the problematization, analysis of the information and the agreement or decision making, as didactic processes of the Social Personnel area._x000D_ The learning strategies were executed considering the interests and needs of the students of the first grade of primary education